Evidence-Based Learning Strategies: Preparing Students With High-Incidence Disabilities for College. (March 2019) - Ray, Amber B.
An increasing number of students with disabilities now attend college, but many do not complete their college program due to poor grades. This may occur because students with high-incidence disabilities often struggle acquiring the academic skills essential to success in college. Teaching learning strategies to students with high-incidence disabilities in high school can help prepare them to be academically successful in college. Learning strategies are specific techniques used to help students approach and learn content material. This article presents five strategies for learning academic content that can be taught to students with high-incidence disabilities who aim to go to college. The learning strategies incorporate mnemonics and an evidence-based practice and are intended to improve students' listening during class, effective note taking, reading content material, assignment completion, and test taking.